1996
DOI: 10.1007/bf00183736
|View full text |Cite
|
Sign up to set email alerts
|

Late follow-up in patients with gastroschisis

Abstract: During a 16-year period, 60 neonates with gastroschisis were treated at the Department of Pediatric Surgery in Graz; 6 died and 54 (90%) survived. A questionnaire was sent to 45 patients, who were called for a medical examination; 31 patients (69%) came to follow-up, 26 of whom reported minor abdominal problems that could be related to gastroesophageal reflux (GER). Fifteen agreed to 24-h esophageal pH monitoring and/or upper gastrointestinal series; in 7 pathological GER could be demonstrated. Manometric stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Lindham described similar results in Swedish patients,6 but fewer North American or Austrian children were affected, which may reflect study methodology or cultural differences 910 Current surgical methods should aim to conserve the umbilicus whenever possible 16…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Lindham described similar results in Swedish patients,6 but fewer North American or Austrian children were affected, which may reflect study methodology or cultural differences 910 Current surgical methods should aim to conserve the umbilicus whenever possible 16…”
Section: Discussionmentioning
confidence: 69%
“…While this observation has been disputed,10 more detailed studies have shown that catch up growth occurs throughout childhood, mostly within the first five years, leading to normal centile ranks in older children 68 9 Children with gastroschisis complicated by intestinal atresia fare less well,8 and both of our subjects with an atresia were below the 25th centile for weight.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…more likely [12,13], the question of whether there is indeed a higher risk for familial recurrence becomes more pressing.…”
mentioning
confidence: 98%